Towards equal opportunities - Molitor, Katharina (Technische Universität Dortmund, 2024)
This cumulative dissertation focused two central educational outcomes – students’ educational attainment (obtaining Abitur) and their well-being (life satisfaction, satisfaction with friends, academic self-concept and helplessness in German). Both outcomes depend on a broad set of predictors, which can be personal (gender, performance), familial (SES, immigrant background, financial cost), motivational (expectation of success, value of education, performance-oriented motivation), stressors (effort, learning stress, parental aspirations) and institutional (enrollment recommendation, school type) and are interrelated with one another. This dissertation thereby builds on the theoretical strands of the expectancy-value theory (Wigfield & Eccles, 2000), the theory of primary and secondary effects of social stratification (Boudon, 1974), the big-fish-little-pond effect (Marsh, 1987), and the self-determination theory (Deci & Ryan, 1983). Key findings based on data of the German National Educational Panel Study (NEPS) are still prevalent educational inequalities, which are partially mediated through motivational factors. Furthermore, differential effects in terms of obtaining Abitur based on the received enrollment recommendation were found, with parental education being more relevant for students without academic-track enrollment recommendation. In terms of students’ well-being while comparing students in different school types but with comparable competence levels differentiating in their enrollment status, it can be stated, that the direct learning environment is more important than being more successful than assessed by teachers. The findings are discussed an implications for practice and research are drawn.
Understanding predictors of educational attainment and well-being in secondary education
Keywords: Educational inequality; Well-being; Motivation; Enrollment recommendation; 370; Chancengleichheit; Bildung; Wohlbefinden